TEKNOLOGI SEDERHANA PEMBUATAN BRIKET ARANG DARI LIMBAH INDUSTRI MEBEL (Simple Technology of Making Charcoal Briquettes from Furniture Industry Waste): Alpian, Wahyu Supriyati, dan Yanciluk - JHT, Admin (Jurnal Hutan Tropika, 2018)
ABSTRACTWaste of the furniture industry activity was not yet utilized optimally. When it developedbecame a produce, it has higher economic value. The potential waste of this furniture industrycan be utilized as raw material for making charcoal briquettes as a source of energy. Charcoalbriquettes are charcoal wood that is altered in shape, size, and density by means of pressing amixture of charcoal powder and adhesive material. Simple technology of making charcoalbriquettes from furniture industry wastes made can be developed to utilize the potential waste ofthe furniture industry as an alternative energy from biomass to sufficient household energyneeds.Keywords: waste, furniture industry, charcoal briquettes, energy, household